Prefusion F, Postfusion F, G Antibodies, and Disease Severity in Infants and Young Children With Acute Respiratory Syncytial Virus Infection. (26th September 2017) - Capella, Cristina; Chaiwatpongsakorn, Supranee; Gorrell, Erin; Risch, Zachary A; Ye, Fang; Mertz, Sara E; Johnson, Sara M; Moore-Clingenpeel, Melissa; Ramilo, Octavio; Mejias, Asuncion; Peeples, Mark E
Abstract : Maternal antibodies to respiratory syncytial virus (RSV) likely play a role in protecting infants from this important pathogen. The concentration and neutralizing activity of serum IgG to the RSV G, and more strikingly the prefusion F, protein confirmed this association. Abstract: Background: Respiratory syncytial virus (RSV) is the most frequent cause of lower respiratory tract infection in infants. Maternally derived RSV-specific antibodies play a role in protection against RSV infection in early life, but data regarding the concentration and specificity of those antibodies are incomplete. Methods: We prospectively enrolled a cohort of previously healthy infants and young children hospitalized (n = 45) or evaluated as outpatients (n = 20) for RSV infection, and healthy noninfected age-matched controls (n = 18). Serum samples were obtained at enrollment to quantify the concentrations and neutralizing activity of serum immunoglobulin G antibodies to the RSV prefusion (pre-F), postfusion (post-F), and G glycoproteins. We also assessed the associations between antibody concentrations and clinical disease severity. Results: Concentrations of pre-F antibodies were ≥3-fold higher than post-F antibodies and >30-fold higher than G antibodies in serum from infants with acute RSV infection. Antibody concentrations and neutralizing activity inversely correlated with age. The pre-F antibodies displayed the greatest neutralizing activity (55%–100%), followed by G (0%–45%), and post-F (0%–29%) antibodies. Higher concentrations of pre-F and G antibodies, but not post-F antibodies, were associated with lower clinical disease severity scores. Conclusions: Maternal antibodies directed to pre-F, followed by antibodies directed to G, can modulate RSV disease severity in young infants.